Effects of COVID-19 pandemic on small & middle-income economies (SMEs) in developing nations: A case study of Narok Town, Kenya - Morompi Ole Masago; Moses Odhiambo Okombo; Sambu Alice; Kweingoti G. Reuben; Bakari Chaka; Bulitia Godrick; Ole Kelele Joshua (Dutch Journal of Finance and Management, 2020)
The COVID-19 pandemic caught many Small and Middle-Income Enterprises (SMEs) unaware and unplanned. The pandemic led to restriction of several economic activities in Kenya; key amongst them transportation, tourism and education. The ripple effect of these restrictions caught up with SMEs, taunted to be a growing economic pillar in Kenya. This study purposed to analyze the exact effect of the pandemic on SMEs in Narok region, Kenya using various economic metrics. The findings were geared to furnish policy makers with the exact economic situation resulting from COVID-19. A case study research design was used with the help of questionnaires, interviews and observations. The researchers found out that most of the entrepreneurs were actually youthful. Commencement of SMEs was largely dependent on the political environment. Most of the SMEs in the region had begun between 2016 to 2018. The number of employees per SME had been effectively reduced to an average of 2 with their daily wages reduced from Ksh. 800 to 200. The pandemic reduced the supply of SMEs stock from other regions into Narok. 82.86% of the SMEs were forced to obtain stock within the county itself. Both the supply of stock to SMEs and their corresponding demand by buyers were drastically reduced by 77.14% and 91.43% respectively. There was however no significant increment in the pricing of the products (P < 0.05). The net profit margins of the SMEs reduced from in excess of Ksh. 20,000 to about Ksh. 5,000 per month. Other auxiliary services such as finance lenders, insurance and marketers were equally affected. About 54.45% of the SMEs were facing dissolution by their owners should the situation persist. In conclusion, the researchers found out that COVID-19 was more of an economic pandemic rather than a health pandemic in the study region. The authors recommend the national and county government to cushion the premises by waiving off some of their taxes.
Keywords: 650; SMEs; COVID-19pandemic; economiceffects